2001
DOI: 10.1046/j.1365-2133.2001.04191.x
|View full text |Cite
|
Sign up to set email alerts
|

A trial of fludarabine and cyclophosphamide combination chemotherapy in the treatment of advanced refractory primary cutaneous T-cell lymphoma

Abstract: These data indicate that the combination of fludarabine with cyclophosphamide may be of clinical benefit in patients with SS but does not affect patient survival. As with other multiagent chemotherapy regimens, bone marrow toxicity is a common and severe side-effect. These data suggest that this regimen should be considered palliative and should be reserved for patients with refractory disease without bone marrow suppression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(21 citation statements)
references
References 23 publications
2
19
0
Order By: Relevance
“…131 Scarisbrick and colleagues studied the efficacy of fludarabine plus cyclophosphamide in 12 patients with advanced CTCL; 8 patients had SS. 52 Five of 8 patients with SS responded, including 1 CR, but bone marrow toxicity was significant. The authors concluded that, although this protocol might offer clinical benefit, there did not appear to be any evidence of improved survival.…”
Section: Chemotherapy Many Different Chemotherapeuticmentioning
confidence: 96%
See 1 more Smart Citation
“…131 Scarisbrick and colleagues studied the efficacy of fludarabine plus cyclophosphamide in 12 patients with advanced CTCL; 8 patients had SS. 52 Five of 8 patients with SS responded, including 1 CR, but bone marrow toxicity was significant. The authors concluded that, although this protocol might offer clinical benefit, there did not appear to be any evidence of improved survival.…”
Section: Chemotherapy Many Different Chemotherapeuticmentioning
confidence: 96%
“…The authors concluded that, although this protocol might offer clinical benefit, there did not appear to be any evidence of improved survival. 52 12.6.2.3. Alemtuzumab.…”
Section: Chemotherapy Many Different Chemotherapeuticmentioning
confidence: 99%
“…It is difficult to compare the results of these studies, some of them being prospective and others retrospec- 29 Foss et al, 30 Scarisbrick et al, 31 Quaglino et al 32 39 Foss, 40 Ho et al, 41 Greiner et al, 42 Cassileth et al, 43 Tsimberidou et al 44 33 tive. Moreover, the methods of assessing response were not the same across studies, and the durations of response were not calculated in the same way.…”
Section: Commentmentioning
confidence: 99%
“…• Several studies have demonstrated potential synergy between purine analogs and alkylating therapies. In one recent study, 12 patients with refractory CTCL received fludarabine and cyclophosphamide [31]. Nine patients had erythrodermic CTCL and three patients had tumor-stage MF.…”
Section: Conventional Chemotherapymentioning
confidence: 99%